Climate evolution during the Pleniglacial and Late Glacial as recorded in quartz grain morphoscopy of fluvial to aeolian successions of the European Sand Belt - Woronko, Barbara; Zieliński, Paweł; Sokołowski, Robert Jan (Geologos, 2015)
We present results of research into fluvial to aeolian successions at four sites in the foreland of the Last Glacial Maximum, i.e., the central part of the “European Sand Belt”. These sites include dune fields on higher-lying river terraces and alluvial fans. Sediments were subjected to detailed lithofacies analyses and sampling for morphoscopic assessment of quartz grains. Based on these results, three units were identified in the sedimentary succession: fluvial, fluvio-aeolian and aeolian. Material with traces of aeolian origin predominate in these sediments and this enabled conclusions on the activity of aeolian processes during the Pleniglacial and Late Glacial, and the source of sediment supply to be drawn. Aeolian processes played a major role in the deposition of the lower portions of the fluvial and fluvio-aeolian units. Aeolian material in the fluvial unit stems from aeolian accumulation of fluvial sediments within the valley as well as particles transported by wind from beyond the valley. The fluvio-aeolian unit is composed mainly of fluvial sediments that were subject to multiple redeposition, and long-term, intensive processing in an aeolian environment. In spite of the asynchronous onset of deposition of the fluvio-aeolian unit, it is characterised by the greatest homogeneity of structural and textural characteristics. Although the aeolian unit was laid down simultaneously, it is typified by the widest range of variation in quartz morphoscopic traits. It reflects local factors, mainly the origin of the source material, rather than climate. The duration of dune-formation processes was too short to be reflected in the morphoscopy of quartz grains.